10 watt-level tunable narrow linewidth $1.5~\unicode[STIX]{x03BC}\text{m}$ all-fiber amplifier. (6th June 2018) - Tang, Ni; Zhou, Zhiyue; Li, Zhixian; Wang, Zefeng
Abstract : We report here a high-power, wavelength tunable and narrow linewidth $1.5~\unicode[STIX]{x03BC}\text{m}$ all-fiber laser amplifier based on a tunable diode laser and Er-Yb co-doped fibers. The laser wavelength can be precisely tuned from 1535 nm to 1580 nm, which covers many absorption lines of mid-infrared laser gases, such as $\text{C}_{2}\text{H}_{2}$, HCN, CO, and HI. The maximum laser power is ${>}$ 11 W, and the linewidth is about 200–300 MHz, which is close to the absorption linewidth of the above-mentioned gases. This work provides a suitable pump source for high-power wavelength tunable mid-infrared fiber gas lasers based on low-loss hollow-core fibers.